Optimalisasi Pendidikan Aqidah Akhlak di Madrasah Ibtidaiyah dalam Membentuk Perilaku Positif Siswa - Hadi Muhaini (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2019)
The education of Aqidah chastity is the process of educating, nurturing, shaping, and providing exercises on morality and good thinking intelligence based on Islamic teachings. This system specifically provides education about Akhlakul Karimah in order to reflect one's personality.Moral education should be given to children as the foundation of the beginning in the face of the reality of the era, so that it can create a strong influence for all stakeholders. Thus, with the education of the children's Aqidah morality will not be easily affected and consider where good and bad behavior. For the results of educational and learning objectives that are expected to be achieved well of course many things to be considered, especially the education problem Aqidah chastity optimally. In addition, the role of teachers is also indispensable, strong human resources and learning strategy should synergize one another. With this, students are expected to apply what they have been in school so that they can be useful in their respective communities.students are expected to apply what they have been in school so that they can be useful in their respective communities.